British American tobacco PLC: an analysis of the group's pricing strategy across its key markets - Mathebula, Peter-Wallace (School of Economics, 2022)
Tobacco products are subject to substantial excise and sales taxes. In most countries these increase over time, but the rate of increase varies between countries and across different types of tobacco products. The tobacco industry is opposed to increases in tobacco taxes, changes in relative tax rates for different tobacco products, and adjustments to excise structures because these adversely affect their profits. However, the tobacco industry can mitigate these shocks by means of its pricing strategies. This paper investigates how the British American Tobacco Group has reacted to excise tax increases and declining industry volumes in order to maintain profitability in its 31 key markets (i.e. key countries) over the period 2006 to 2019. The Group's most common response to the excise tax increases was to overshift the excise increases. This meant that the retail price was increased by more than the increase in the excise tax. In a scenario of decreasing sales volumes and shifting consumer preferences, it is the relatively price-inelastic demand for the Group's products and its substantial market power which often make this strategy possible and successful. However, even though this strategy is most common, the trading environment differs in each market, which meant that the Group had to sometimes apply different strategies. These strategies include undershifting the tax (especially for cheaper brands), oversupplying the market in anticipation of excise increases, timed price changes, and adjusting product attributes in response to regulatory changes. Furthermore, as traditional combustibles are coming under increased pressure, the Group is developing new product categories.